ERROR ANALYSIS ON HAN CHARACTER STROKE WRITING (汉字 HÀNZÌ) OF MANDARIN LANGUAGE TEACHERS (Participants on Training for Senior High Schools/Vocational Schools/ Islamic High Schools Chinese Language Teachers on Critical Literacy and Hots) - Mulawarni Mulawarni (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
ABSTRACT Mandarin language has been one of the subjects in 2013 Curriculum as one of the foreign languages taught in schools starting from elementary to universities. Due to high interest in Chinese language in opening career opportunities to people who can master the language, there is also an increase of interest on not only the language but also on how to teach the language. Teachers in this context the teachers of Mandarin language at least master the basic of teaching Mandarin language in the five elements. On this matter, there are errors in the writing of Han Characters that occurs during the learning process on learners and teachers. The errors cover the strokes misalignment on written texts of describing oneself. This study analyzes the common mistakes of Chinese stroke writing on Teachers of Chinese language teachers in Indonesia on training programmes. Key Words: Han Characters; Error Analysis in writing; writing misalignment; Chinese stroke writing and Mandarin Language Teachers.